2017
DOI: 10.1177/0263395717737887
|View full text |Cite
|
Sign up to set email alerts
|

Voting in the Eurovision Song Contest

Abstract: The Eurovision Song Contest is not only the largest song contest worldwide but also probably the world’s largest election for a non-political office. In this article, we are interested in the voting behaviour of Eurovision viewers. Do they vote sincerely, strategically according to rational choice assumptions (i.e. for the song they believe will be the likely winner) or for another song? Using data from a large-scale survey carried out in Europe, we find interesting voting patterns with regard to these questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(57 reference statements)
0
4
0
1
Order By: Relevance
“…Collectively, these 'other' voters constituted 37% of the respondents, while sincere and bandwagon voters were 26% each and strategic voters comprised the minority at 11%. Stockemer et al (2018) conclude that Eurovision voters are influenced by affective factors other than musical preference. While the sample is limited, it nevertheless demonstrates the potential and the need for further studies into the meaning audiences themselves assign to their votes.…”
Section: Europe Start Voting Now! Eurovision And/as Political Partici...mentioning
confidence: 84%
See 1 more Smart Citation
“…Collectively, these 'other' voters constituted 37% of the respondents, while sincere and bandwagon voters were 26% each and strategic voters comprised the minority at 11%. Stockemer et al (2018) conclude that Eurovision voters are influenced by affective factors other than musical preference. While the sample is limited, it nevertheless demonstrates the potential and the need for further studies into the meaning audiences themselves assign to their votes.…”
Section: Europe Start Voting Now! Eurovision And/as Political Partici...mentioning
confidence: 84%
“…However, the majority of these studies rely on a quantitative analysis of voting results; although they remain useful for identifying broad patterns, these do not provide qualitative insight into whether the actual voting decisions of viewers align with the theories of cultural and political proximity that emerge from these studies. Stockemer et al’s (2018) survey of Eurovision viewers’ voting behaviours is a welcome exception to this literature. Based on a survey of 500 Eurovision viewers in Germany, France and the UK, the study identifies four types of voting: sincere voting, where a person simply votes for their favourite song; strategic voting (voting for their preferred entry among the handful of likely winners rather than a personal favourite); bandwagoning (voting for the expected winner regardless of personal preference); and ‘other’ voters who do not fit into the previous three types, but may use other reasons, such as language affinity, ethnic or diaspora voting or neighbourhood/proximity voting.…”
Section: Introductionmentioning
confidence: 99%
“…Such an improved model is likely to give a better fit to the data and to give even higher estimates of the amount of expatriate voting. Stockemer et al (2018) suggest that 36% of tele-voters may be engaging in expatriate voting, or regional voting, or preferences for specific countries. This is in line with our experimental results, and can generate large scores for otherwise unpopular songs.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns in audience votes in Eurovision have been widely studied. It is often seen as being influenced by ‘bloc voting’ or ‘buddy voting’, reflecting geo-political affiliations and regional clusters (Bjornberg, 2007: 17; Stockemer et al, 2018). Other studies have found that voting is also linked to the quality of the participants as well as linguistic and cultural proximities between singers and voting countries (Ginsburgh and Noury, 2008).…”
Section: Conclusion: Master Narrativesmentioning
confidence: 99%